(3JNWjW h eQGbHI GdGfJGL aj GdeDSSGJ GdUfGYjI h GdNOejI (B/s - (3YGeQ, SGeM YHO GdeWdHs; (3SjO bfOjd, YdGA eMeO s ((3YeGf(B: s (3OGQ GdacQ(B, s, 2011)
(3eaghe h CSS GOGQI GdGfJGL h GdYedjGJ , ENJjGQ GdehbY h GdJNWjW GdOGNdj ddeUfY , JNWjW h JfXje GdGfJGL aj GdeDSSGJ GdUfGYjI h GdNOejI , GdJfHD HMLe GdGfJGL , LOhdI h JMejd GdGfJGL , JUeje h JWhjQ GdefJLGJ , GdQbGHI Ydi GdYedjGJ aj VhA fXe JcGdja GdGfJGL , GdQbGHI Ydi GdGfJGL , UjGfI GdCUhd GdGfJGLjI , GdcaGAI GdGfJGLjI , Jbjje COGA GdbWGY GdUfGYj (B( (3GdeTcdGJ h GdMdhd(B) (3, OhQ EOGQI GdGfJGL aj ehGLgI GdJMOjGJ GdeYGUQI , EOGQI GdLhOI ceONd dJMSjf caGAI GdGfJGLs
(3eQGLY U(B.431s
Keywords: (3EOGQI GdGfJGLs; (3GdJNWjWs; (3GdQbGHIs; (3GdeDSSGJ GdUfGYjIs